Determination of the relationship between the characteristics of LED lamps by calculation methods - I. E. Vasileva; A. G. Saybel (Омский научный вестник)
The article presents results of the task statement and results of the research of the functional relationship of parameters of LED lamps in relation to the modern concept of quality management in an industrial enterprise. The regression dependencies obtained for the complete and truncated sets of the studied objects are described. Graphic illustrations of the identified dependencies are presented, which make it possible to predict the parameters of lamps at the early stages of designing lighting systems for special-purpose objects contributing to the optimization of decision-making on the organization and management of production.